Cr2(NCN)3, a ferromagnetic carbodiimide with an unusual two-step magnetic transition. (17th November 2016) - Sterri, Kjersti B.; Besson, Claire; Houben, Andreas; Jacobs, Philipp; Hoelzel, Markus; Dronskowski, Richard
Abstract : Crystallographic and magnetic characterization of a ferromagnetic transition-metal carbodiimide with an unusual two-step magnetic phase transition. Abstract : While most transition-metal carbodiimides exhibit antiferromagnetism, chromium(iii ) carbodiimide, the first transition-metal(iii ) carbodiimide with a 3d 3 configuration, displays ferromagnetic coupling. We report here on a neutron-diffraction study of Cr2 (NCN)3 demonstrating that a complete three-dimensional ferromagnetic order is established below T = 114 K. Complementary ac and dc susceptibilities as well as electron paramagnetic resonance (EPR) and heat-capacity measurements allow us to further analyze its magnetic properties, elucidating another magnetic transition around T = 160 K. We describe here a magnetic two-step transition scenario over an unusual wide temperature range, from paramagnetic to a lower-dimensional ferromagnetic ordering, presumably a 2D-ordering within the chromium layers, below T LD = 166(4) K and from this low-dimensional ordering to a complete 3D-ferromagnetic ordering below T C = 114 K.